2017
DOI: 10.1037/bar0000043
|View full text |Cite
|
Sign up to set email alerts
|

Computerized behavioral skills training with selection-based instruction and lag reinforcement schedules for responses to interview questions.

Abstract: This study evaluated the efficacy of a computerized behavioral skills training (CBST) program for teaching responses to interview skills by adolescents and young adults with learning disabilities. The package consisted of instructional videos, video modeling, rehearsal, feedback, and selection-based instruction. A multielement design was incorporated within each tier of the multiple-probe design such that each question was pseudorandomly assigned to a CBST condition or a CBST plus selection-based instruction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…These findings partially replicate previous research on recommended methods for job interview training for this population. For example, prior research on the use of video feedback for interview training showed improved performance (Kern-Dunlap et al, 1992;Moore, 2015;Morgan & Salzberg, 1992;O'Neill, 2015). In the present study, although accurate responding increased for some participants following implementation of the video feedback component with InterviewStream©, participant responses remained stable after a second and third session with this component of the training package.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…These findings partially replicate previous research on recommended methods for job interview training for this population. For example, prior research on the use of video feedback for interview training showed improved performance (Kern-Dunlap et al, 1992;Moore, 2015;Morgan & Salzberg, 1992;O'Neill, 2015). In the present study, although accurate responding increased for some participants following implementation of the video feedback component with InterviewStream©, participant responses remained stable after a second and third session with this component of the training package.…”
Section: Discussionsupporting
confidence: 40%
“…Sessions were scheduled one to two times per week, based on the availability of the participants and experimenter, and lasted no more than 75 min. A trained confederate reports indicating these are among the most commonly asked interview questions (Moore, 2015;O'Neill, 2015).…”
Section: Setting Materials and Dependent Variablementioning
confidence: 99%
“…Future research might examine the addition of programmed prompts during SB instruction that might promote variable novel TB responses (e.g., that was a great answer, can you think of any other relevant information?). Finally, further examination of the effects of SB instruction and lag reinforcement schedules in the context of computerized BST for responses to interview questions (O'Neill & Rehfeldt, 2016), as well as other types of complex conversational skills (Aguirre, O'Neill, Rehfeldt, & Boyer, 2014), is warranted due to the paucity of research on SB instruction for people with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, visual feedback tethered to prior handwashing offers individualized supplemental prompts not present in video models, which could be especially important for students with IDDs. However, video modeling integrated with behavioral skills training can be very effective in teaching accurate response topographies (O’Neill & Rehfeldt, 2017).…”
Section: Discussionmentioning
confidence: 99%